2004
DOI: 10.1002/hep.20056
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypertonic sodium chloride on intracranial pressure in patients with acute liver failure

Abstract: Acute liver failure (ALF) is a rare condition characterized by the development of encephalopathy in the absence of chronic liver disease. Cerebral edema occurs in up to 80% of patients with Grade IV encephalopathy. In the current prospective randomized controlled clinical trial, we examined the effect of induced hypernatremia on the incidence of intracranial hypertension (IH) in patients with ALF. Thirty patients with ALF and Grade III or IV encephalopathy were randomized. Patients in Group 1 (n ‫؍‬ 15) receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(158 citation statements)
references
References 37 publications
2
148
1
7
Order By: Relevance
“…24 Finally, in patients with acute liver failure and grade IV hepatic encephalopathy, the administration of hypertonic saline to increase serum sodium concentration reduces the incidence and severity of intracranial hypertension compared with a control group of patients receiving the standard of care. 25 Hepatorenal syndrome was also strongly associated with low serum sodium concentration in our series (17% in patients with serum sodium Յ130 mmol/L compared with 10% in patients with serum sodium 130-135 mmol/L and only 6% in patients with normal serum sodium concentration) ( Fig. 2 and Table 5).…”
Section: Discussionsupporting
confidence: 53%
“…24 Finally, in patients with acute liver failure and grade IV hepatic encephalopathy, the administration of hypertonic saline to increase serum sodium concentration reduces the incidence and severity of intracranial hypertension compared with a control group of patients receiving the standard of care. 25 Hepatorenal syndrome was also strongly associated with low serum sodium concentration in our series (17% in patients with serum sodium Յ130 mmol/L compared with 10% in patients with serum sodium 130-135 mmol/L and only 6% in patients with normal serum sodium concentration) ( Fig. 2 and Table 5).…”
Section: Discussionsupporting
confidence: 53%
“…35 About 25% of patients with ALF in a report from India had hyponatremia, which was prominent in patients with severe encephalopathy. 4 However pathogenesis of hyponatremia in ALF is unclear.…”
Section: Aggravating Factors Of Encephalopathy In Acute Liver Failurementioning
confidence: 99%
“…66 In a recent prospective randomized trial involving 30 patients with ALF, it was found that use of hypertonic (30%) sodium chloride infusion to maintain serum sodium levels between 145 and 155 mmol/L led to a significant decrease in ICP. 35 …”
Section: Ammonia Lowering Strategiesmentioning
confidence: 99%
“…Low sodium levels are related to the impairment of renal solute-free water excretion most likely due to an increased vasopressin secretion, which results in increased sodium retention and reduced renal free water clearance, which predispose to life threatening conditions in the cirrhotic such as HRS and refractory ascites [36] . Also, hyponatremia represents an independent risk factor for brain edema, a fatal complication of acute liver failure [37,38] . Interestingly, we found that low sodium levels were associated with mortality at 30 and 90 d. Also, HRS was associated to mortality in the univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%